Analisis Kualitas Pelayanan Penerbitan Rekomendasi Izin Usaha Mikro Pada Kantor Camat Lae Parira Kabupaten Dairi - Andy Penta Gracia Simbolon; Badaruddin Badaruddin; Nina Siti Salmaniah Siregar (PERSPEKTIF, 2022)
The purpose of the study was to determine and analyze the quality of service for issuing micro business license recommendations and their constraints at the Lae Parira sub-district office, Dairi Regency. The research method used in this research is descriptive qualitative method, which is a method that only describes situations and events that aims to systematically describe the characteristics of a population or certain fields in a factual and accurate manner without looking for or explaining a relationship. The results of the study found that the quality of service for issuing recommendations for micro business licenses at the Lae Parira District Office of Dairi Regency was still not good. This can be seen from the complaints of the public or micro business actors who require licensing recommendations so that the general public has a negative view or picture of the agency. The constraint factors faced in improving the quality of services for issuing recommendations for micro business licenses are: the presence of officers who seek to obtain personal benefits from the licensing recommendation service process, employees do not try to avoid a negative public image of the institution so that many people are reluctant to deal with business administration, and lack of employee commitment to improving service quality so that employees tend to prioritize personal matters over service work to the community